Sizing methodology for hybrid systems based on multiple renewable power sources integrated to the energy management strategy - Feroldi, Diego Hernán (2014)
This work presents a design methodology for a hybrid energy system based on multiple renewable power sources and bioethanol. The new concept of generation consists on having multiple power sources such as a PEM fuel cell system fed by the hydrogen produced by a bioethanol reformer and wind-solar sources working all together supervised by the energy management system. The necessary heating for the bioethanol reforming reaction can be provided by the renewable sources to enhance the efficiency of the hydrogen production. It is worth noting that, from the power balance as well as backup point of views, the hybrid system is equipped with energy storage devices. An optimal sizing methodology integrated with the energy management strategy is proposed here for designing the overall hybrid system. The suggested approach is based on genetic algorithms, using historical climate data and load demands over a period of one year. Several simulation results are given to show the methodology performance in terms of loss of power supply probability (LPSP), costs and bioethanol consumption